Xavier Zubiri’s Polemics with Phenomenological Concept of Religion - NIZIŃSKI, SERGIUSZ (Filozofia Chrześcijańska, 2018)
Zubiri does not accept the classical phenomenological concept of religion which unites religion with sacrum. He is constructing his own metaphysical concept of religion which he unites with the power that has reality. According to Zubiri, religion has its origin in power of the real which allows a person to have personal life. Zubiri’s concept of religion allows to evaluate particular religions acknowledging that they may be more or less true. It is impossible for phenomenology of religion.